MASS MEDION TOOLS AND ITS CHARACTERISTICS, DEVELOPS - Ahmedov Azimjon Ilhomovich the teacher of Andijan State Institute of Foreign Languages,; Asqarov Dostonbek, Isroilova Gulchiroy, Abdusalomova Mushtari, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
Abstract: Mass media is any type of media that can be distributed to the masses. Because it’s consumed by the masses and not just the elites, some may argue that it’s a form of low culture. Keywords: Mass Media Examples, newspapers, television, magazines, websites, book, radio.